Gastric Plexiform Fibromyxoma Resected Using Nonexposed Endoscopic Wall-Inversion Surgery: A Case Report - Masahide Ebi (Case Reports in Gastroenterology, 2022)
Gastric plexiform fibromyxoma is extremely rare. In our case, upper gastrointestinal endoscopy of a 41-year-old woman patient revealed a 1-cm submucosal tumor (SMT) in the greater curvature of the lower body of the stomach. On contrast-enhanced computed tomography, the tumor was hypervascular in the arterial phase with continuous enhancement in the post-venous phase. On endoscopic ultrasonography, it had a low echo pattern. The preoperative diagnosis was a gastric SMT with a rich vasculature; however because the biosy specimen did not contain tumor tissue, a malignant tumor could not be excluded. The patient underwent nonexposed endoscopic wall-inversion surgery (NEWS), and the tumor was completely resected. Immunohistochemical examination revealed that the tumor was positive for D2-40 and α-smooth muscle actin, but negative for c-kit, discovered on gastrointestinal stromal tumor-1, desmin, S100, Melan-A, signal transducer and activator of transcription 6, insulinoma-associated protein 1, CXCL13, ETS transcription factor, follicular dendritic cell, anaplastic lymphoma kinase, human melanoma black, h-caldesmon, and CD1a, 10, 21, 23, 31, 34, 68, and 163. Approximately, 1–2% of the tumor cell nuclei were Ki-67-positive. Finally, we diagnosed the tumor as a plexiform fibromyxoma. In conclusion, NEWS is an effective method for the treatment of SMTs with a diameter of <3 cm.